Ancaman Fenomena Perkosaan Korektif terhadap Human Security di Afrika Selatan - Mochtar, Yusnan Hadi; Indriastuti, Suyani; Dwi E., Linda (e-Sospol, 2016)
Abstract One of the most problematic problems faced by South African Lesbians is corrective rape phenomenon. This action is done by particular people to cure and make them being real South African Women. Real South African Woman is when a woman turns to be heterosexual, a mother and taking care of children. It is believed that it is not a humanisctic action and threats the lesbian security. As an unsolved problem, lesbian is being alienated when it occurs. Lesbian cannot access security because government does not consider this problem seriously. In fact, South Africa is one of the most progressive countries in glorifying human right idea. It is proven by 1996 South African Constitution which forbids discrimination based on personal identity preferences, especially sexual orientation. In this case, this study will analyze threats of corrective rape phenomenon toward human security, specifically lesbians by using liberal feminist theory. It is more interesting to use the theory because this phenomenon relates to gender-based violence which becomes the concern of feminists. The analysis is about how it can happen. It uses government points of view on how government works in practical level leading to that process.